Influence of deodorization temperature on formation of tocopherol esters and fatty acids polymers in vegetable oil. Issue 3 (8th June 2016) - Kreps, František; Kyselka, Jan; Burčová, Zuzana; Schmidt, Štefan; Rajchl, Aleš; Filip, Vladimír; Ház, Aleš; Jablonský, Michal; Sládková, Alexandra; Šurina, Igor
Abstract : The paper describes laboratory deodorization of rapeseed oil (Ro), model sunflower (SoM), and model rapeseed (RoM) oils, its effect on the tocopherol content and the kinetics of tocopherol degradation. We now present a novel approach to analysis of alpha‐tocopherol degradation product as well as kinetic study esters of alpha‐tocopherol with fatty acids and alpha‐tocopheryl quinones. Alpha‐tocopherol esters were found to be the principal products of tocopherols degradation in high temperature experiment. A laboratory deodorization, lasting 2 h caused formation of 70–128 mg/kg of alpha‐tocopherol esters in model oils and 25 mg/kg of alpha‐tocopherol esters in rapeseed oil without modification. The commercially available sunflower and rapeseed oils contained 3–12 mg/kg of alpha‐tocopherol esters. The alpha‐tocopherol esters are formed at higher rate than alpha‐tocopheryl quinone, which was unstable at high deodorization temperature. Tocopherols took no part in non‐radical thermal reactions, taking place in second high‐temperature experiments with oxygen‐free atmosphere. We proved by DART TOF‐MS the formation of polymeric fatty acids via Diels–Alder reaction taking place in heated oils. Practical applications: Although an extensive research have been conducted in the area of high‐temperature degradation of tocopherols, this is the first report on formation of fatty acids esters of tocopherols during oil deodorization. The proof of their presence in deodorized oils, deodorization condensates, deep‐fried foods, and oils constitutes a breakthrough. We ingested them as yet unknowingly. Their degradation is not nearly as fast as that of tocopherol itself or its oxidation products. In the course of their hydrolysis in stomach tocopheryls of fatty acids could thus become the source of unoxidized tocopoherols. We found out that during laboratory deodorization of vegetable oils were formed esters of tocopherols with fatty acids. During heating of oils are free fatty acids the acid catalyst of esterification. Abstract : We found out that during laboratory deodorization of vegetable oils were formed esters of tocopherols with fatty acids. During heating of oils are free fatty acids the acid catalyst of esterification.